Evaluation and Management of Women who Have Experienced Stillbirth in Their Previous Pregnancies - Erdem Fadiloglu; Atakan Tanacan; Canan Unal; Mehmet Sinan Beksac (Gynecology Obstetrics & Reproductive Medicine)
Objective: To evaluate the subsequent pregnancy outcomes of women who have experienced unexplained stillbirth in their previous gestations.